Pattern of poisoning cases in a teaching hospital in Western Nepal - Kishore, PV; Palaian, S; Paudel, R; Mishra, D; Ojha, P; Alam, K; Mishra, P (Journal of Institute of Medicine Nepal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Introduction: Poisoning is a common problem in Nepal. Data from the Western region of Nepal are lacking. The present study analyzed the clinical profile and the management pattern of poisoning cases admitted to the Manipal Teaching Hospital (MTH). Methods: The poisoning cases treated at Manipal Teaching Hospital from January 2003 to June 2006 were studied. Results: A total of 98 poisoning cases (0.51% of Emergency department admissions) were treated (female 54.08 %) and age group 21-40 years (44.90 %). Nearly one third (32.65%) reached the hospital with in two hours of poison consumption. The median (interquartile range) duration of the hospital stay was 4 (2) days. The poisoning was intentional in 79.59% cases. The route of exposure was mainly oral (96.94%). Rat poison was the commonest poison (31.68%) followed by drugs (22.77%). Majority (83.67%) received symptomatic treatment. Secondary complications were observed in 28.57% and the overall fatality rate was 18.37%. Rat poison was responsible for 5 deaths. Nearly two thirds (65.31%) of the total cases received psychological counseling. Conclusion: Similar studies covering different hospitals conducted over a long period are needed to confirm our findings. Keywords: Drug over dosage, Poisoning profile, Rodenticide, Western Nepal. Journal of Institute of Medicine, April, 2008; 30:1 26-34 The full text of this paper is available from the Journal of Institute of Medicine website